Upper mantle convection driving by density anomaly and a test model - 傅容珊 王景赟 常筱华 黄建华 戴志阳 查显杰 (Acta seismologica sinica, 2005)
A mathematic-physical convection model in upper mantle is established in this paper. This model is in a three dimensional frame. Assume that the density anomalies, which are mapped from the seismic tomography data, are responding to the temperature perturbation in the connective system. This model takes the density anomalies as the driving force for the mantle convection. We solve the basic equations with different boundary conditions in a domination of wave number by using the FFT arithmetic. In order to test the validity of our theory and method two simple models (higher-lower density body and break off slab) are employed to calculate their flow patters in this paper. Results show that our method can be directly used to investigate the upper mantle convection patterns and its related problems of lithospheric dynamics.[PUBLICATION ABSTRACT]